Primary Basic Subject by Fission - Neelameghan, A. (Journal of Information and Knowledge, 1973)
The formulation of the initial set of Basic Subjects the schedule of Traditional Primary Basic Subjects for use in a scheme for library classification, is discussed. The mode of formation of such a Basic Subject is deemed to be by Fission of the universe of subjects. Guiding principles used in the Colon Classification ir arranging the Primary Basic Subjects in a helpful sequence are mentioned with ilulstrative examples.